Shooting Profile of Female Petanque Riau Athletes Judging from Time Effectiveness - Efdi Gusdillah; M. Fransazeli Makorohim (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
Petanque is a sport that is still developing, so it is understandable that there are still changes to the regulations. By frequently looking for information related to regulations and attending seminars or workshops related to petanque regulations, it is hoped that we can always get the latest information regarding these regulations . This research is an interview and observation technique as well as a literature review technique, aiming to reveal "whether or not there is a shooting profile for Riau petanque athletes in terms of time effectiveness ." The data collection technique used in the literature review is by collecting various references and references that are relevant to the topic of the problem being researched, using the Google Scholar database by entering words. From the source search results in the database, 5 articles were obtained which were published from 2014 to 2021. The conclusion of this research shows that "There is a Profile that exists in the sport of Petanque, so it can be used as study and input. For other people as a reference , as research material.